Land and Urban Policies for Poverty Reduction : Proceedings of the Third International Urban Research Symposium Held in Brasilia, April 2005, Volume 1 - Freire, Mila; Lima, Ricardo; Cira, Dean; Ferguson, Bruce; Kessides, Christine; Mota, Jose Aroudo; Motta, Diana (World Bank, Washington, DC and Institute for Applied Economic Research, Brasilia, 2014)
The first paper of this section (Durand-Laserve) documents how increasing pressures on urban land and the 'commodification' of shelter and settlement has increased 'market evictions' of families holding intermediate tide to property, although international declarations and pressures have contributed to reducing 'forced evictions.' The second paper (Mooya and Cloete) uses the tools of the New Institutional Economics to analyze the argument in Hernando DeSoto's path-breaking book, The Mystery of Capital, that full legal tide is the key to turning 'dead capital' in the form of informal property held by many low-income families into an economic asset and to detonating broad-based economic growth. The paper concludes that intermediate forms of tenure can have the virtues of full legal tide if properly constructed, and then examines the case of Namibia in this context. The third paper (Fernandes) documents and assesses the recent efforts of the Brazilian federal Ministry of Cities to develop a comprehensive approach for regularizing title throughout that country. In the fourth paper, Abramo gives a structural and theoretical over-view of informal settlement in Brazil. The fifth paper (Rakodi) looks at traditional land delivery systems in five medium-sized Sub-Saharan African cities, and concludes that policies and programs can build on their strengths.